FLOUTING MAXIM ON SUSI COURT-PROCEEDINGS ANSWER OF FERDY SAMBO CASE - Ramadhanti, Novia Zahra; Heryono, Heri (Jurnal Penelitian Humaniora, 2024)
This paper is about a pragmatic study of the flouting maxim that appears in the court proceeding of Ferdi Sambo’s maid, Susi. The objectives of this paper are (1) to identify the category of flouting maxims that appear in Susi’s answer to her court proceedings, and (2) to find out what the reason is for the appearance of those flouting maxims that Susi breaks. This research used a descriptive-qualitative approach. In analyzing the data, this study used the theories of Grice, 1975 and Cutting (2002 as reasons theory. This research also used the theories of George Yule, 1996 and Levinson (2013) to support the research. The writer found 25 utterances that flout the four categories of maxims from the source data. Which are, the maxim of quantity, the maxim of quality, the maxim of relevance, and the maxim of manner. The dominant flouting maxims that appear are maxims of quality and quantity, with 40% for quality and 28% for quantity, while the others have the same amount of calculation, which is 16% for the flouting maxim of relevance and 16% for the flouting maxim of manner. There are several reasons why these flouting maxims appear, such as overstatement, understatement, irrelevant statements, and ambiguous statements.